A Diffusion‐‐Reaction Competition Mechanism to Tailor Lithium Deposition for Lithium‐Metal Batteries. (1st April 2020) - Chen, Xiao‐Ru; Yao, Yu‐Xing; Yan, Chong; Zhang, Rui; Cheng, Xin‐Bing; Zhang, Qiang
Abstract: Lithium metal is recognized as one of the most promising anode materials owing to its ultrahigh theoretical specific capacity and low electrochemical potential. Nonetheless, dendritic Li growth has dramatically hindered the practical applications of Li metal anodes. Realizing spherical Li deposition is an effective approach to avoid Li dendrite growth, but the mechanism of spherical deposition is unknown. Herein, a diffusion‐reaction competition mechanism is proposed to reveal the rationale of different Li deposition morphologies. By controlling the rate‐determining step (diffusion or reaction) of Li deposition, various Li deposition scenarios are realized, in which the diffusion‐controlled process tends to lead to dendritic Li deposition while the reaction‐controlled process leads to spherical Li deposition. This study sheds fresh light on the dendrite‐free Li metal anode and guides to achieve safe batteries to benefit future wireless and fossil‐fuel‐free world. Abstract : Sphere factor : A diffusion–reaction competition mechanism reveals the principle of spherical Li deposition. By controlling the rate‐determining step of Li deposition, different Li deposition scenarios are revealed, in which the diffusion‐controlled process tends to give dendritic Li deposition while the reaction‐controlled process leads to spherical Li deposition.